2021
DOI: 10.1155/2021/1961134
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Height and Tilt Angle of the Solar Receiver for a 30 kWe Solar Tower Power Plant for the Electricity Production in the Sahelian Zone

Abstract: This work investigated the prediction of the optimum height and tilt angle of the solar receiver of a 30 kWe solar tower power plant for the electricity production in the Sahelian zone. Initially, the solar field is sized to determine the total reflecting surface area of the mirrors and the number of heliostats. A PS10-like radially staggered heliostat field is used to design the heliostat layout in the field using a Matlab code. The concentrated solar flux at the input of the receiver was determined using Sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…The central tower system is thought to be the least expensive technology in large-scale energy generation [7]. A solar tower power (STP) plant produces electricity by focusing and reflecting direct normal irradiation through mirrors named heliostats onto a central receiver, which is located at the top of the solar tower, in which a heat transfer fluid absorbs and transports the heat to generate electricity via a thermodynamic conversion system similar to that of conventional power plants [7,8]. The solar field is a critical subsystem of STP systems since it contributes approximately 50% of the total cost of the plant and 40% of the total energy losses [8].…”
Section: R Peer Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The central tower system is thought to be the least expensive technology in large-scale energy generation [7]. A solar tower power (STP) plant produces electricity by focusing and reflecting direct normal irradiation through mirrors named heliostats onto a central receiver, which is located at the top of the solar tower, in which a heat transfer fluid absorbs and transports the heat to generate electricity via a thermodynamic conversion system similar to that of conventional power plants [7,8]. The solar field is a critical subsystem of STP systems since it contributes approximately 50% of the total cost of the plant and 40% of the total energy losses [8].…”
Section: R Peer Reviewmentioning
confidence: 99%
“…where A tot (m 2 ) is the total area of the heliostat and A sh,bl (m 2 ) is a shaded or blocked heliostat area. The total solar power input on the field (Q s inc ), the reflected power to the receiver (Q r ), and the absorbed power by the receiver (P) was calculated by (7), (8), and (9), respectively [27], respectively.…”
Section: Blocking and Shadowing Efficiencymentioning
confidence: 99%
“…They concluded that the organic working fluids evaporate at low temperatures, and thus it is possible to take advantage of the thermal energy wasted in factories and solar energy. Also, choosing the operating liquid is significant in improving the efficiency of ORCs [45][46][47][48][49]. Simulation of ORCs requires a numerical analysis in which mass-energy balance equations, heat transfer, pressure drop, and thermodynamic properties of organic liquids are implemented [50][51][52][53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%